Custo Brasil: um comparativo de uma indústria de selos de vedação e suas plantas fabris brasileira e norte-americana - Cabral, Sergio Ricardo Carvalho (2016)
One of the major challenges for Brazil is that of overcoming the barriers that confine it the status of a developing country. However, in order for Brazil to reach an acceptable level of economic development it is necessary that the country face up to the serious structural problems preventing its growth. The Brazil cost, a term used to express issues such as high interest rates, deficient infrastructure, extremely high tax burden, excessive bureaucracy among others, has become the main hindrance to overcome. This paper proposes to identify the main elements that, according to industry sectors are the main cause of the systemic inefficiency in Brazil. Besides, in order to demonstrate how the Brazil cost affects the local industry’s competitiveness in relation to its foreign competitors, a comparative study between a company, whose parent plant is based in the United States of America, and its Brazilian subsidiary will be presented. This paper has adopted the causal comparative research methodology, collecting data straight from the partners, directors and employees of a mechanical seals industry, both in Brazil and the United States of America. This research seeks to identify how the Brazil cost, taking into account only five items (taxes, salaries/wages, energy, investment and raw materials) influences the costs of a mechanical seal produced in the country, as well as the main factors that impairs competitiveness on the local plant. The conclusion reached is that the Brazil cost hinders the local production to such an extent that, even though the exchange rate is strongly depreciated in relation to the American dollar, the national product is significantly more expensive than the same product manufactured in the North American facilities